2014
DOI: 10.1097/fjc.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vascular PI3K/Akt-NOX Signaling Underlies the Peripheral NMDAR-mediated Pressor Response in Conscious Rats

Abstract: The molecular mechanisms for peripheral N-Methyl-D-Aspartate receptor (NMDAR)-mediated vascular oxidative stress and pressor response are not known. We conducted integrative (in vivo) and ex vivo biochemical studies to test the hypothesis that ROS-dependent calcium influx, triggered by activation of vascular kinases, underlies the NMDAR-mediated pressor response. Pharmacological inhibition of PI3K/Akt (Wortmannin; 15 μg/kg), PKC (Chelerythrine; 5 mg/kg, i.v.), Ca2+ influx (nifedipine; 0.35 or 0.75 mg/kg) or NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
(66 reference statements)
2
12
0
1
Order By: Relevance
“…5), consistent with our recent findings in the same tissue (McGee & Abdel-Rahman, 2012, 2014) and in other tissues (Gunasekar et al, 1995). In agreement with reported findings (Krenz & Korthuis, 2012; Yogi et al, 2010), ethanol produced modest, but significant increases in ROS, at least partly, via its oxidative metabolites, acetaldehyde and acetate (Deng & Deitrich, 2007; Seitz & Stickel, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…5), consistent with our recent findings in the same tissue (McGee & Abdel-Rahman, 2012, 2014) and in other tissues (Gunasekar et al, 1995). In agreement with reported findings (Krenz & Korthuis, 2012; Yogi et al, 2010), ethanol produced modest, but significant increases in ROS, at least partly, via its oxidative metabolites, acetaldehyde and acetate (Deng & Deitrich, 2007; Seitz & Stickel, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…The latter conclusion gains credence from recent findings that the Ca 2+ entry blocker nifedipine caused dose-dependent attenuation of the pressor response caused by peripheral NMDAR activation in conscious rats. 59 …”
Section: Nmdar Signalingmentioning
confidence: 99%
“…42, 53, 59,57 Despite the widespread distribution of the different NOX isoforms in cardiovascular tissues, 84 the possible contribution of NOX to peripheral NMDAR-mediated ROS and its functional relevance remained unknown until very recently. Data generated in our laboratory showed that pretreatment with the nonspecific NOX inhibitor, apocynin, attenuated the ROS production in vasculature, and pressor response caused by peripheral NMDAR activation.…”
Section: Nmdar Signalingmentioning
confidence: 99%
See 2 more Smart Citations